Integrating Orange - For higher sweetpotato production in the Eastern Province of Zambia - International Potato Center (2013)
Access to timely, quality sweetpotato planting vines in the Eastern Province of Zambia can improve food security and nutrition, especially during times of drought, crop disease, and hunger. The Integrating Orange project has established at 37 sites fields across five districts with 37 recently trained decentralized vine multipliers (DVMs), who are currently receiving quality orange-flesh sweetpotato vines for multiplication and distribution next growing season. Working with the Katopolo Farm Institute and local extension services, the project aims to increase women’s participation through vine multiplication, processing and preservation, as well as commercial production to include greater than 60% female participants.